Α-Conotoxin GI triazole-peptidomimetics: potent and stable blockers of a human acetylcholine receptor12. Issue 6 (4th December 2018) - Knuhtsen, Astrid; Whitmore, Charlotte; McWhinnie, Fergus S.; McDougall, Laura; Whiting, Rachel; Smith, Brian O.; Timperley, Christopher M.; Green, A. Christopher; Kinnear, Kenneth I.; Jamieson, Andrew G.
Abstract : A conotoxin peptidomimetic was developed as a potential muscle relaxant that is highly potent and blood plasma stable. Abstract : The potency and selectivity of conotoxin peptides for neuropathic receptors has made them attractive lead compounds in the development of new therapeutics. Specifically, α-conotoxin GI has been shown to be an unparalleled antagonist of the nicotinic acetylcholine receptor (nAChR). However, as with other peptidic leads, poor protease resistance and the redox instability of the conotoxin scaffold limit bioactivity. To counter this, we have employed the underutilised 1, 5-disubstituted 1, 2, 3-triazole to act as a structural surrogate of the native disulfide bonds. Using an efficient, on-resin ruthenium azide-alkyne cycloaddition (RuAAC), each disulfide bond was replaced in turn and the biological activities quantified. One of the mimetic isomers exhibited a comparable activity to the native toxin, while the other showed no biological effect. The active mimetic isomer11 was an order of magnitude more stable in plasma than the native GI. The NMR solution structure of the mimetic overlays extremely well with the structure for the native GI demonstrating that the triazole bridge is an exceptional surrogate for the disulfide bridge. Development of this potent and stable mimetic of GI leads us to believe that this strategy will yield many other new conotoxin-inspired probes and therapeutics.